It's not rocket science : - Anderson, Dave (John Wiley and Sons, 2015)
Showing you how to stop chasing hot trends and start driving real growth, this guide offers a commonsense approach to business success and outlines a basic, effective, and actionable four-step blueprint for building a great organization of any size, in any arena.